How HR Analytics Shapes Financial Decision-Making: The Mediating Role of Managerial Information Quality and the Moderating Effect of Digital Capability in the Hotel Industry - Yayan Sugiarto; Raden Intan Media Ratna Puri; Dewi Fitriani (LPPM Institut Pendidikan Nusantara Global, 2026)
The hotel industry increasingly relies on data-driven managerial practices to improve operational and financial effectiveness. However, prior studies have predominantly examined HR analytics in relation to HR performance and organizational outcomes, while its role in financial decision-making remains underexplored. This study aims to examine the effect of HR analytics on financial decision-making in the hotel industry, mediated by managerial information quality and moderated by digital capability. A quantitative explanatory approach was employed using a cross-sectional survey design. Data were collected from 234 respondents working at 78 three- and four-star hotels in Bandung and the surrounding areas, including hotel managers, HR managers, finance managers, supervisors, and hotel administrators with at least 3 years of work experience. The data were collected between January and February 2026 using an online questionnaire distributed through Google Forms and measured using a five-point Likert scale. The proposed model was analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS software. The findings indicate that HR analytics positively influences financial decision-making and managerial information quality. Managerial information quality was also found to significantly mediate the relationship between HR analytics and financial decision-making. In addition, digital capability significantly strengthens the relationship between HR analytics and managerial information quality. The novelty of this study lies in integrating HR analytics, managerial information quality, digital capability, and financial decision-making into a single framework in the hospitality context. The study contributes to hospitality management literature by emphasizing the strategic role of analytics and digital capability in improving managerial and financial practices. Nevertheless, the findings are limited to hotels located in Bandung and the surrounding regions.